Embodied Experience in British and French Literature, 1778–1814 - Heydt-Stevenson, Jillian (Cambridge University Press, 2025)
Combining feminist, materialist, and comparatist approaches, Jillian Heydt-Stevenson reveals evocative and hidden information about objects like diamonds, hats, and statues, demonstrating women's life-preserving ecological, social, and political connections to material things in literature from the late eighteenth and early nineteenth centuries.